Protective effects of Marinobacter nauticus strain GH3 exopolysaccharide on the Oreochromis niloticus model for Alzheimer’s disease - Ghada Abdel-Razik; Mohamad Abdelrazik; Alaa Rashad; Wagdy K. B. Khalil; Fagr Kh. Abdel-Gawad; Ahmed A. Hamed; Mohamed E. El Awady (Scientific Reports)
Abstract Marinobacter nauticus strain GH3 was isolated from the Red Sea, Sharm Elshiekh, and classified according to cultural attributes, biochemical properties, and the analysis of genetic relationships using 16 S rRNA sequences. A substantial proportion of exopolysaccharides (EPS) in GH3-EPS contained a sulfate content of 25.4%, uronic acid (12.18%), and N-acetylglucosamine (13.6%). The composition of monosaccharides in this fraction consists of glucose, glucoronic acid, arabinose, and xylose by 2:4:3:3, respectively. SEM showed a flower-like shape with white bundles on the GH3-EPS surface. GH3-EPS enhancement of the RAW264.7 macrophage line RAW 264.7 ATTC number J774 cell proliferation via MTT assay for cell viability. GH3-EPS had a high stimulation effect on releasing TNF-alpha and IL-10. Followed by its effect against cyclooxygenase (COX-2) and lipoxygenase (LOX), with IC50s of 14.74 and 19.4 µg/ml, respectively. Antioxidant activity was evaluated for GPx-4, GSS, and MDA with highly significant results, and for DPPH, ABTS, and iron chelating with IC50 (43.51, 31.27, and 84.96 µg/ml, respectively). AChE was inhibited by a mean of 52.92 ± 4.54 and 68.22 ± 5.64 µg/ml. In a fish animal model, GH3-EPS demonstrated a positive treatment effect for AD, supporting biochemical studies, histopathology for some brain parts, and toxicity.